A NARRATIVE REVIEW OF POST-CORONARY ARTERY BYPASS GRAFT MYOCARDIAL ISCHEMIA AND INFARCTION. - Bharti, B. B. (Student's Journal of Health Research Africa, 2023)
Patients with obstructive coronary artery disease are advised to undergo coronary artery bypass graft (CABG) surgery to enhance survival and quality of life. Patients receive arterial and venous implants to enhance coronary blood flow. There are factors that can cause periprocedural myocardial necrosis and factors that can cause late recurrent angina following CABG. In this article, an endeavor is made to examine these particulars.